THE INFUENCE OF THE BIBLE ON ENGLISH LITERATURE - Maratova Farangiz; Komiljonova Mavlyuda Abduvalievna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The Bible being the Holy Words of God is the sacred book of the Christians. The literary influence of the Bible has been tremendous, all pervasive and perennial. In fact the Bible has been providing the English men of letters spiritual themes and also modulated their literary style. It has gifted ample vocabulary, most beautiful quotations, maxims and phrases. The whole range of English language and literature is much indebted to the Bible for its dignity and richness.